NEOLIBERALISM: A SUBJECTIVE AND OBJECTIVE BASIS FOR POPULISM - Lopes Izaguirre, Willian (Revista Gênero e Interdisciplinaridade, 2023)
Populism is present in the current political scenario in a modern way associated with neoliberalism. The objective of this work is to associate the subjective impacts produced by neoliberal policies on the individual, mainly the feeling of competition and the vision of work as a source of profit and, no longer of exchange, with the rise of right-wing populism in the last decade as a response to the crises of the capitalist system itself, largely due to the inefficiency of the political left in offering strong answers. The methodology chosen is based on the critical association of texts by Foucault, Dardor, Laval and Ruzza, in which a dialogue between subjective aspects of the individual and the macro structure of current politics will be promoted.